Studi Tundaan Perjalanan Kendaraan Di Simpang Bersinyal Yang Terintegrasi Dengan Palang Pintu Kereta Api - Tristono, Tomi (JURNAL AGRI-TEK, 2014)
This paper talked about model of scheduling trip to vehicle traffic at a signalized intersection. There is a train track on one arm. Construct the model of schedulling trips at signalized intersection integrated with train door stop. The methods of scheduling trips transition used fuzzy logic. The result of simulation represented time scheduling trips transition model of vehicle traffic flow. The scheduling had significant time result although the jamming problem can?t be solved directly. Degree of Saturation of traffic would decrease slowdown step by step at some regular cyclus after transition cyclus. Finally the degree of saturation would be limited to normal degree.Keywoords scheduling trip, vehicle traffic train track and intersection integrated